Development of high thermal conductivity UO2–Th heterogeneous fuel. (September 2018) - Ševeček, Martin; Kubáň, Jan; Valach, Mojmír; Škoda, Radek
Abstract: A novel design of heterogeneous UO2 –Th nuclear fuel for light water reactors (LWRs) is proposed. The main advantages of the design are higher thermal conductivity, reduced maximal temperature in the fuel, lower heat stored in the fuel system, or higher thermal breeding ratio. Thermal, neutronics and simple economics calculations were performed to determine the benefits of the new fuel concept. Moreover, an experimental setup utilizing flashing method for measuring of thermal characteristics was designed. It will serve to confirm theoretical assumptions and to precisely determine thermal conductivity and heat capacity of the proposed fuel design and to assess thermal resistance between UO 2 pellets and Th plates. The many substantial benefits of the proposed fuel design are reached with very competitive cost, which is also estimated. Highlights: New heterogeneous nuclear fuel design which takes advantages of combination of both materials UO 2 and thorium is proposed. Projected experimental setup based on the flashing method can be utilized for experimental evaluation of the new fuel concept. The benefits of proposed design include lower maximal temperature or lower heat stored for a very competitive cost.